P12 Sustainability: staff knowledge of which items of waste can be recycled in the orthopaedic operating theatre. (22nd July 2022) - Peacock, C; Liu, P; Gurung, B; Fu, H; Phoon, K; Afzal, I; Sochart, D; Kader, D; Asopa, V
Abstract: Introduction: NHS England generates over 20 million tonnes of CO2 per year, representing 4% of the nation's greenhouse gas emissions. One third of all hospital waste comes from operating theatres. Our aim was to investigate the degree of knowledge of sustainable waste segregation amongst theatre staff in an elective orthopaedic centre and identify ways to improve their waste segregation practice. Methods: Over a one-week period, 20 randomly selected theatre staff of different roles, completed a questionnaire asking them which disposal bin 11 commonly used orthopaedic theatre items should be placed in – general waste or recycling. After initial data collection, posters specifically identifying recyclable items were created and displayed in each operating theatre. Following this intervention, data was re-collected from another 20 randomly selected theatre staff using the same questionnaire. Results: Results from the initial questionnaire showed general waste and recyclable items were correctly identified by staff in 65% (78/120 responses) and 59% (59/100 responses), respectively. Following the educational intervention, the percentage of correct responses increased to 68.3% (82/120 responses) and 85% (85/100 responses); i.e. staff knowledge of what can go into a recycling bin improved by 36%. Conclusion: Educating staff by placing posters in the operating theatre can improve knowledge of what orthopaedic theatre items can be recycled and is a simple and effective way of producing sustainable change in surgery. Guiding and empowering individuals to exercise sustainable practice in the operating theatre will help the NHS to overcome the significant challenge of achieving net zero carbon by 2045. Take-home message: Educating staff by placing posters in the operating theatre is a simple and effective way of improving waste segregation practice and will help the health service to overcome the significant challenge of achieving net zero carbon.